2012
DOI: 10.1039/c2dt30312d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a tris(2-hydroxyphenyl)methane-based cryptand and its triiron(iii) complex

Abstract: Reaction of tris(5-amino-2-ethoxy-3-isopropylphenyl)methane and pyridine-2,6-dicarbonyl-dichloride affords a multi-dentate cryptand in 48% yield. Metallation with iron(III) chloride results in a substantial conformational change of this ligand to give a trianionic triiron(III) complex. Ferric cations line the periphery of the internal cavity with each adopting a square pyramidal N(3)Cl(2) coordination environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This conclusion was supported by EPR analysis of the oxygenated complexes, which showed the signal for a mononuclear Cu­(II) center and the remaining two Cu­(II) centers linked by hydroxo groups. Magnetic studies revealed a ferromagnetically coupled Cu­(II)­Cu­(II) center along with an isolated Cu­(II) in these complexes . Although these tricopper complexes do not typically support hydrocarbon oxidation, they represent a popular approach to the problem, and ligand-assisted formation of trinuclear complexes has been reported for other metal ions such as manganese, iron, cobalt, and zinc, as well. …”
Section: Toward the Development Of A Biomimetic Catalystmentioning
confidence: 86%
“…This conclusion was supported by EPR analysis of the oxygenated complexes, which showed the signal for a mononuclear Cu­(II) center and the remaining two Cu­(II) centers linked by hydroxo groups. Magnetic studies revealed a ferromagnetically coupled Cu­(II)­Cu­(II) center along with an isolated Cu­(II) in these complexes . Although these tricopper complexes do not typically support hydrocarbon oxidation, they represent a popular approach to the problem, and ligand-assisted formation of trinuclear complexes has been reported for other metal ions such as manganese, iron, cobalt, and zinc, as well. …”
Section: Toward the Development Of A Biomimetic Catalystmentioning
confidence: 86%
“…Herein, we report that a family of triiron complexes housed within a tris­(β-diketiminate) cyclophane effect the catalytic conversion of N 2 to N­(SiMe 3 ) 3 using KC 8 and Me 3 SiCl. Notably, the series of complexes span varying oxidation states and ancillary bridging ligands (see Figure ) allowing for the first systematic evaluation of the effect of nitrogenase-relevant ancillary ligands on dinitrogen activation. Our results demonstrate that the noncyclophane donors are labile under reducing conditions as a putative μ 3 -nitridotriiron­(II) complex is observed as a major and common product of most reactions.…”
mentioning
confidence: 85%
“…Similar observations have been made previously in the case of similar metallocryptand systems. 47,48 However, we cannot discount potential weak electrostatic couplings between each Mn center. Negligible differences in the electrochemical features were observed between complexes 1 and 1c, leading us to suggest that each Salen moiety within the cryptand structure 1 acts as a discrete entity and does not influence the redox potentials of the other Salen subunits.…”
Section: ■ Results and Discussionmentioning
confidence: 99%